Préserver les herbiers de zostères face aux mouillages sauvages : la difficile construction d’une politique environnementale sur l’île de Ré - Jérôme Cardinal; Christelle Audouit; Caroline Rufin-Soler (VertigO, 2022)
This article is based on a study carried out in 2019 on the island of Ré concerning illegal mooring on eelgrass beds, a habitat that has been preserved since 1992 by the “Habitat Directive”. The thorny issue of illegal mooring on the island has been revived through the issue of the damages it causes to eelgrass beds. In the context of the Charente coastline, and more particularly the Ré island, the article analyses the construction process of an environmental policy to regulate the mooring impact on eelgrass beds. This process crosses political, environmental and economic issues mobilising heterogeneous actors at different decision-making levels. The agenda setting and local policy making - by setting up light dedicated Mooring Zones (french « Zones de Mouillages et d’équipements Légers » (ZMEL)) - are conflicting. It gives rise to controversy and blockages by the various stakeholders (sailors, locally elected representatives and decentralized State departments) which can only be understood by considering the socio-historical context of the area. The difficult emergence of this environmental policy is highlighted by the interaction of successive administrative reforms - transforming the organization and prerogatives of decentralized State departments -, the representations of sailors, the fuzzy governance frame of the eelgrass beds, and local political games and its power relations.